NEMATOSIT KARANG Montipora undata (SCLERACTINIA) DARI PANTAI MALALAYANG TELUK MANADO - Priskila S Kodoati; Carolus P Paruntu (JURNAL PESISIR DAN LAUT TROPIS, 2021)
The aim of this study was to know the nematocysts composition of Montipora undata (Scleractinia) which was collected in the Malalayang coastal coral reef, Manado Bay. This research was conducted for three months, from October to December 2020.  Observation of nematocysts was done under an Olympus CX41 microscope with a magnification of x100 objective lens connected to a computer equipped with the application of Optica view 7 at the Laboratory of Fish Health, Environment and Toxicology, Faculty of Fisheries and Marine Sciences, UNSRAT.  The results showed that  M. undata had the main nematocyst composition, namely microbasic b-mastigophore (MbM) of 60.0 %, small microbasic p-mastigophore type II (sMpM-II) 26.67 %, small holotrichous isorhiza (sHI) 6 ,67 %, large holotrichous isorhiza (lHI) 4.44 %, and large microbasic p-mastigophore type II (lMpM-II) 2.22 %.  MbM is the dominant type of nematocyst for this coral species.  Further studies are suggested to investigate the function of MbM and morphology of nematocysts of various types of corals in the genus Montipora.Keywords: Composition, Manado Bay, Montipora undata, nematocyst, Scleractinia